Cause and outcome of poisoning among admitted patients in a teaching hospital (Bangladesh Medical Journal Khulna, 2020)
Background: Pesticide containing organophosphous compound (OPC), copper sulphate (cuso4), harpic, savlon, are easily available allowing opportunities for easy source of poisoning in the southern part of Bangladesh.Objective: This study was aimed to find out epidemiological characteristics of patient presenting with poisoning & the outcome of poisoning.Methods: This hospital based prospective cross sectional study was conducted from July to December 2017 in medicine ward among poisoned males and female patients. Sample size was 150 and they were selected from the population by non probability sampling technique.Results: Among 150 cases OPC are (70,46.66%) followed by sedative drug (21,14%), Harpic (19,12.66%) Street poison (15,10%) copper sulphate (12, 8%) Rat killer (3,2%) Kerosene (2,1.33%) Paracetamol (3,2%) Puffer fish (1,0.66%) Yaba (1,0.66%) other's (3,2%). In this study young age group 21-30 yrs was the most common (41%) victim of poisoning, female to male ratio was 1.32:1. Majority of the patients hailing from rural area (63%) and most of them (33,38.59%) had secondary level of education. Familial disharmony (45%) was the commonest background for poisoning. Study showed that 82% of the patients recovered completely during follow up and 7% patient developed complication. Mortality rate was 11%.Conclusion: OPC poisoning is the commonest poisoning. Early hospitalization, severity assessment & prompt institution of appropriate therapy can make a favorable outcome.Bang Med J (Khulna) 2019; 52 : 30-34